Agroecosystem complexity of Surjan and Lembaran as local farming systems effects on biodiversity of pest insects (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Trisnawati DW, Nurkomar I, Ananda LK, Buchori D. 2022. Agroecosystem complexity of Surjan and Lembaran as local farming systems effects on biodiversity of pest insects. Biodiversitas 23: 3619-3629. Farming systems can influence the diversity and abundance of insect pests. This study was conducted to determine the effect of Surjan and Lembaran farming systems on the diversity and abundance of insect pests in Kulon Progo, Yogyakarta. The field survey was conducted in three Surjan paddy fields and three Lembaran paddy fields in Panjatan Subdistrict, Kulon Progo Regency. The sampling of pests was collected using four kinds of traps, such as sweeping net, yellow sticky trap, pitfall trap, and yellow pan trap. The traps were set twice in the vegetative phase and twice in the generative phase. The results showed that the abundance of pests in Surjan paddy fields was not different from that in Lembaran paddy fields. However, the number of pest species in Surjan paddy fields was higher than in Lembaran paddy fields. In addition, the structure and composition of pests in both farming systems were significantly different. Hemiptera was the most common insect in both farming systems, with dominant pest species of Nephotettix virescens and Nilaparvata lugens.